Morbidity and mortality associated with tumour-related hindquarter amputation: a review of 23 cases - Sharifudin, Mohd Ariff; Wan Ismail, Wan Faisham Numan; Wan, Zulmi; Mat Zin, Nor Azman; Mohamed Amin, Mohamed Azril; Goh, Kian Liang (2014)
Background: Hindquarter amputation, the removal of the entire lower limb along with the ipsilateral pelvic bone, is reserved for malignant or aggressive tumours located in the proximal lower extremity. With the advancement in limb salvage surgery (LSS), it is reserved for palliative surgery or when LSS is contraindicated. This report aims to review the morbidity and mortality associated with this procedure in the treatment of pelvic bone and soft tissue tumours. Methodology: Patients with bone or soft tissue tumour involving the pelvis who underwent hindquarter amputation at any point in their clinical course between year 2000 and 2010 were reviewed. Patients were recruited from a single oncology referral institution. Results: Twenty-three patients were included in this review, consisted of 17 males and 6 females with mean age of 40.1 (range 8 to 79 years old). Ten patients underwent surgery for palliation. Classical type of pelvic resection was performed on 11 patients while others were subjected for modified (6), extended (5) and compound (1) type. Commonest underlying pathology was pelvic osteosarcoma (5 patients). Majority of wounds (47.8%) were primarily closed with posterior myocutaneous flap. There was one perioperative death due to sepsis with lung complications. The average follow-up was 13 months (range 2 to 109 months). Eight patients were still alive on their last follow-up, 9 died due to advanced stage of disease, while 3 died of other causes. Commonest complications observed were wound-related. All patients had poor functional outcome on their recent follow-up. Conclusion: Hindquarter amputation remains an important option with considerable morbidity and is indicated for only minority of far-advanced tumours. It offers a chance of palliation and possibly cure when lesser surgical options have been exhausted.